Radio meteor physics – a comparison between techniques from 1945 to the mid-1970’s - Hocking, W.K.; Kolomiyets, S.V. (Radiotekhnika, 2020)
A description of the physics of radar meteors from 1945 to the mid-1970s is presented. Concrete designs of various radars in different countries are presented. Harvard project is the best documented of these early radars, and we will focus on that radar. Application of multi-receiver stations for orbit determination became relatively common, especially with the advent of the IGY in 1957. Canada also built the Springhill Meteor Observatory around the time of the IGY, but of special note was the construction of several meteor radars in the USSR. The contribution of Kashcheyev and his scientific group to the development of radar meteor technologies was emphasized. A discussion of some equipment options of Balakleya geophysical complex in different years was held. Problems of meteor radar technologies in solving problems of astronomy and geophysics are noted. "Meteor winds" became a mainstay of upper atmospheric research into dynamical processes after 1960’s. Such research was undertaken at multiple sites all over the "Western" global arena as well as in the USSR. In attention is paid to the history of changes in the methods of obtaining, processing and storage of meteor information. Some aspects of the application of innovative technologies in meteor radar systems were discussed, primarily in the study of winds and atmospheric circulation in the meteor zone. The advent of personal computers, plus the somewhat simultaneous development of digitizers in the early 1970’s, was a major breakthrough for many areas of scientific research and Meteor studies. This work is the first part of a planned review of radar meteor physics and related technologies from 1945 to 2020.